2015
DOI: 10.1111/trf.13193
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of human immunodeficiency virus Type 2 (HIV‐2) in a multiplex transcription‐mediated amplification assay does not affect detection of HIV‐1 and hepatitis B and C virus genotypes: a multicenter performance evaluation study

Abstract: The change in the oligonucleotide design of the Ultrio Elite assay to enable HIV-2 detection has not affected the analytical sensitivity for the other viruses regardless of the genotype. Genotype reference panels are instrumental to compare the sensitivity of nucleic acid test assay versions and could serve as an alternative to seroconversion panels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…However, discriminatory testing, which delayed the result by about 4 h, was required only in a single blood donor with an initially false-reactive result. This excellent specificity after the initial test run (99.99%) was slightly better than reported for the older Ultrio assay (99.83%) with semi-automated handling [13] and for the Ultrio Elite assay (99.95%) in a multicenter study [14]. Excellent results on specificity and robustness as well as the short turnaround time of the Procleix Ultrio Elite assay / Panther system suggested that ID-NAT seems to be feasible in the future also for granulocyte donors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, discriminatory testing, which delayed the result by about 4 h, was required only in a single blood donor with an initially false-reactive result. This excellent specificity after the initial test run (99.99%) was slightly better than reported for the older Ultrio assay (99.83%) with semi-automated handling [13] and for the Ultrio Elite assay (99.95%) in a multicenter study [14]. Excellent results on specificity and robustness as well as the short turnaround time of the Procleix Ultrio Elite assay / Panther system suggested that ID-NAT seems to be feasible in the future also for granulocyte donors.…”
Section: Discussionmentioning
confidence: 91%
“…It should be pointed out that LODs for HBV DNA (WHO standard 97/750) are low and almost identical for the Ultrio Elite ID-NAT (4.3 IU/ml, 95% fiducial limits 3.8-5.0 IU/ml) and the Ultrio Elite discriminatory HBV assay (4.5 IU/ml, 95% fiducial limits 4.0-5.3 IU/ml). The low LOD of the Ultrio Elite assay was confirmed (4.6 IU/ml, 95% fiducial limits 3.8-5.9 IU/ml) by a multicenter performance study [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid amplification testing (NAT) identifies a nucleic acid sequence thought to occur only once within the agent being tested. However, the “clinical sensitivity of NAT methods can be improved by dual region detection or addition of redundant oligonucleotides to avoid detection of genetic variants of viruses.” This confounds the quantitative nature of these tests, making it difficult to determine whether each reaction detects a single virus. NAT does not provide information about the nonidentified remainder of the genome.…”
Section: Viral Quantitation and Terminologymentioning
confidence: 99%
“…There is no generally agreed method to relate these different values. Grabarczyk et al reported that 1 IU is equivalent to 5.33 copies of hepatitis B virus (HBV), 2.73 copies of HCV, and 0.58 copies of HIV, but does not explain the basis of these conversion factors. Kleinman et al, assume three to four copies of HCV per IU but do not reference the source of this conversion.…”
Section: Viral Quantitation and Terminologymentioning
confidence: 99%
“…In a study performed by the German Red Cross Blood Donor Service and the Centro de Hemoterapia y Hemodonacíon de Castilla y León, the 95% LODs of the MPX v 2·0 were 43·3 and 50·6 IU/ml for HIV, 3·9 IU/ml and 17·6 IU/ml for HCV and 1·1 IU/ml and 3·5 IU/ml for HBV, respectively . Grabarczyk and colleagues evaluated Ultrio Plus and Ultrio Elite and found a 95% LOD of 22·3 (CI 19·3–26·2) and 23·5 IU/ml (CI 20·2–27·7) for HIV, 6·3 IU/ml (CI 4·9–8·5) and 7·3 IU/ml (CI 5·7–10·1) for HCV and 4·7 IU/ml (CI 3·9–5·9) and 4·6 IU/ml (CI 3·8–5·9) for HBV, respectively. The South African National Blood Service (SANBS) recently evaluated the new cobas MPX and the Ultrio Elite assays by performing replicate testing on dilution panels made from NAT‐positive, seronegative donations and neat donations made from seropositive, NAT‐negative donations previously detected by the Tigris Ultrio Plus/Abbott Prism combination.…”
Section: Analytical Sensitivitymentioning
confidence: 99%